Doctor-patient remote consultation system with secure medical images - Teh, Yee Heng (2022)
In this rapid developing world, everything around us has becoming more and more digital related. Therefore, our privacy data is all over the Internet. This will make us become more vulnerable to cyber-crime and illegal data exploitation. Hence, security of our privacy information had becoming a tricky trouble to deal with. However, data in words had been found that are easier to be encrypted. But, multimedia data such as video, audio and image are the example of data which are harder to be encrypted. Hence, this kind of data had ‘rarer’ security compared to words. The most often security used recently in today’s industry is watermarking those multimedia data. However, watermarking can work on image and video only. Also, watermarking still available for people to view those data but prevent them from exploiting due to copyrights. However, if people who wish to make the data to be viewable by certain people only such as X-ray image of certain important people, watermarking probably will be not enough to accomplish that. Furthermore, people living in rural area often cannot access to hospital or medical help easily and immediately. Therefore, the objective of this project is to develop a system which can restrict the right to access to image data and using image encryption algorithms to protect those images to be extract by unauthorized person as well as helping people living in rural area to get medical consultation easier than before. In this project, students and lecturer from Faculty of Medicine and Health Science had become our target users. The image encryption technique that might involved were scrambling and diffusion. The outcome was that we can encrypt the X-ray image and the people with decryption key only can view the image. In the experiment phase, 3 of the selected algorithms was implemented as similar language as possible to produce more reliable result. The result was recorded including the run time and encrypted image size. The final selection of the algorithms depended on the encryption size and computation speed. The smallest size with the fastest computational speed was selected and through the result, the selected algorithm was DNA encoding.